Model â€œThe Best Proccesâ€ Pendidikan Bermutu dan Berdaya Saing - Suwarjono Suwarjono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
The rationale of this article is based on the quality of the school and the quality of the graduates is still low, the implementation of sentaralistic education, the school management is not appropriate, the input-output analisys approach, the community participation is still weak, and cooperation is still low. Then the required management model that can create a quality education and competitive. Model